ATIVIDADE ANTIMICROBIANA E ANTIBIOFILME DE EXTRATOS DE LÚPULOS(Humulus lupulus L.) CULTIVADOS NO BRASIL - Motta, Caroline de Souza (2022)
Biofilms formation and permanence in food production chain is an important factor inthe incidence of foodborne diseases. Consequently, the study of biofilm inhibitoryagents has become a fundamental area of research. The antimicrobial activity of hop(Humulus lupulus L.) is already known. However, despite being a crop with greatgrowth potential in the country, the existing information about the antimicrobialproperties of hops grown in Brazil is still scarce. This study evaluated theantimicrobial and antibiofilm activities of hydroethanolic extracts of hops from Comet,Polaris and Brewers Gold varieties, produced in Brazil. Analyzes were performed todetermine the Minimum Inhibitory Concentration of the extracts, inhibition halo test,anti-adhesion activity with crystal violet, exopolysaccharides quantification, andScanning Electron Microscopy (SEM). The α- and β- acids levels ranged from 0.39 to1.07%. Gram-positive bacteria showed greater susceptibility to extracts whencompared to Gram-negative ones. The crystal violet adhesion assay revealedexpressive anti-adhesion activity against Listeria monocytogenes, Staphylococcusaureus, Escherichia coli and Salmonella Typhimurium. Comet variety extract reducedthe adhesion of S. aureus and S. Typhimurium by 95% and 90%, respectively.Extractsof the three varieties significantly reduced the exopolysaccharide productionby S. aureus. The micrographs obtained by SEM show a reduction in cellconcentration and damage to the cell membrane, confirming hop extracts'antibacterial and antiadhesion effects. These results support the potential of usingxi hops grown in Brazil as an anti-adhesion agent to control biofilm formation in the foodindustry.